Investigating the use of AI-based Tools among High School Students in the Partium Region. Results of an experimental Micro-research (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Education is undergoing a radical shift. Students are embracing Artificial Intelligence (AI) tools that go beyond traditional learning aids. Interaction with AI can enhance learning skills and help students to develop critical thinking, problem-solving, algorithmic thinking, and tech literacy. They also can boost productivity with the help of virtual assistants; manage schedules, organization, and time. This growing trend of AI-powered learning fuels our research. We aim to explore the impact of these tools on education by examining both traditional e-learning technologies and their AI-powered counterparts. This survey lays the groundwork for a larger study investigating how high school students utilize Information and Communication Technology (ICT) tools. Our research targets high school students in the Partium region, namely Bihor and Satu Mare counties, located along the northern Hungarian-Romanian border. This multilingual and religiously diverse region is home primarily to Romanians and Hungarians, with significant Romani populations and smaller Slovak and Swabian communities. This unique mix offers potential for future comparative analyses and a valuable opportunity to explore educational trends. To initiate this exploration, we have conducted by now a micro-survey among students at the theoretical high school in Săcueni, a central town within the region.